Keadilan Restorative dalam Perkara Pidana Berdasarkan Peraturan Mahkamah Agung No. 1 Tahun 2024 Presfektif Teori Hukum Pembangunan - Ickbal Hofifi Bairuroh; Sarman Sarman; Husein Manalu (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
Restorative Justice in the criminal justice system at the court level after the issuance of Supreme Court Regulation (PERMA) Number 1 of 2024 concerning Guidelines for Adjudicating Criminal Cases Based on Restorative Justice. This approach shifts the focus from retribution (retributive justice) to victim loss recovery, offender accountability, and social relationship restoration. This study uses the perspective of the Developmental Law Theory (Teori Hukum Pembangunan) by Mochtar Kusumaatmadja, which views law as a tool of social engineering to achieve national development goals, including legal reform that is aligned with Pancasila values. PERMA No. 1 of 2024 is consistent with the spirit of the Developmental Law Theory because it aims to realize humane, benefit-oriented law enforcement, and prioritizes conflict resolution that accommodates the interests of all parties, in accordance with the values of justice and balance existing in the community. The implementation of this PERMA is a concrete effort to reform Indonesian criminal law to build a justice system that is more responsive to the real needs of the community